Knowing tourists behavior: the imperative for successful marketing strategy in tourism - Senić, Radoslav; Milojević, Sonja (Hotel and Tourism Management, 2017)
Studying the nature of consumer behavior, in particular the behavior of tourists, has always been rather complex. The issue becomes even more complicated due to the pace of environmental changes, and consequently the factors that have an impact on tourists behavior. The purpose of the paper is to identify the distinctions between standard consumer behavior and behavior of a tourist by looking into purchasing decision making process concerning products and services.